ANTI-INFLAMMATORY ACTIVITY OF CILACAP-ORIGINAL Virgin Coconut Oil (VCO) USING THE PROTEIN DENATURATION METHOD - Utami, Tri Fitri Yana; Asep Nurrahman; Fatikah (Gamma Publishing, 2025)
Inflammation is the body's attempt to deactivate or destroy invading organisms, eliminate irritation, and prepare the stage for tissue repair. Many anti-inflammatory agents can be used, one of which is Virgin Coconut Oil (VCO). This study aims to determine the anti-inflammatory potential of original Cilacap VCO using the protein denaturation method. Furthermore, absorbance measurements were carried out using UV-Vis Spectrophotometry. The anti-inflammatory potential of VCO using the protein denaturation method has an IC50 of 14.05 ppm, which is categorized as very strong because it has a range of <50. This proves that VCO has the potential as an anti-inflammatory.